Inhibition effects of ionic and non-ionic derivatives of imidazole compounds on hydrogen permeation during carbon steel pickling - Silva, Matheus G.; de Araujo, Rodrigo G.; Silvério, Raquel L.; Costa, Alberto N.C. [UNESP]; Sangi, Diego P.; Pedrosa, Leandro F.; da Fonseca, Gláucio S.; da Silva, Ladário; Coelho, Lilian W.; Ferreira, Elivelton A. (My University, 2022)
Hydrogen embrittlement can occur when atomic hydrogen is absorbed by steel during the acid cleaning process. In the literature, studies of corrosion inhibition by organic compounds in acid solutions have not given attention to the inhibition of hydrogen permeation in the steel. In this work, we show that the best corrosion inhibition does not always indicate the best hydrogen permeation inhibition. For the first time, imidazole-based compounds were studied as hydrogen permeation inhibitors during carbon steel pickling in hydrochloric acid at high concentration (5.4 mol L−1). The immersion of steel in solutions containing 250 mg L−1 of the inhibitors 1-butyl-3-methylimidazolium tetrafluoroborate ([Bmim]BF4) and 1-butyl-3-methylimidazolium chloride ([Bmim]Cl) resulted in low corrosion inhibition efficiency of approximately 18% in both cases. On the other hand, the hydrogen permeation inhibition efficiency was 59%. The addition of 2-(nitromethylene) imidazolidine (IMD) and 2-(nitromethylene) oxazolidine (OXA) to HCl solutions provided corrosion inhibition efficiencies of 46.7% and 24.4%, respectively. However, these compounds did not present hydrogen permeation inhibition effects.
Keywords: Corrosion inhibition; Devanathan-Stachurski cell; Diffusion coefficient; Hydrogen permeation inhibition; Imidazole-based compounds; SAE 1020 steel